Erosi Tanah Dan Strategi Konservasi Tanah - Anggita Puspita Sari; Febrianti Astutiningsih; Wahyu Kurniawati (Journal Innovation In Education, 2024)
Erosion or erosion is the erosion of the earth's crust caused by water, ice or wind. Soil erosion is a threat that can occur at any time so there is a need for land conservation strategies to overcome it. Soil conservation is the placement of each plot of land in a way of use that is appropriate to the soil's capabilities, which aims to eliminate negative impacts such as erosion. The aim of this research is to provide information about soil erosion and land conservation strategies. In writing this article, we used the literature study method so that the information was obtained from various bibliographic sources, such as books, scientific articles and journals.